Dissemination of the study on public art to primary schools at the state of EspíritoSanto - Torquatro, Jaqueline; Fraga Nunes, Fabíola; Cirilo, Aparecido José; de Miranda, Giuliano (Guará Journal, 2023)
This article shares aspects of the extension project’s initiative to provide basic education teachers in Espírito Santo with preservation and conservation strategies for urban monuments based on affective learning. This study was developed by the UFES Arts Extension and Research Laboratory (LEENA), to propagate information on public art in Espírito Santo through dissemination of the website artepublicacapixaba.com. The theoretical production on this topic, published on the same website, is developed based on an educational kit distributed to schools located at Espírito Santo. The extension project seeks to preserve the memory of the history and art of Espírito Santo, in addition to encouraging discussion about the ways of representing cultures and personalities that were part of the territorial, social and cultural formation of the state. It is discussed the discrepancy in monuments that represent the history of European colonization in the state versus portrayals of other ethnicities, such as enslaved Africans and indigenous peoples. The study is intended to promote emotional connections between students, teachers, researchers, and the community in general with monuments and their historical context.